Isotopic composition and thermal regime of ice wedges in northern Victoria Land, East Antarctica - RAFFI, Rossana; B. Stenni (Permafrost and Periglacial Processes, 2011)
Ice wedges, with tops located 27 to 55cm below the ground surface, were studied over several summers between 1998 and 2006 at three sites with differing elevations in northern Victoria Land, East Antarctica. The thermal regime, based on data-logger measurements over five years, exhibits very low temperatures, an inferred absence of snow, and high temperature gradients between the ground surface and the top of the ice wedge that may trigger cracking. A co-isotopic study of the wedge-ice oxygen (δ18O) and hydrogen (δD) isotopic values shows extremely negative deuterium excess values and a strong divergence from the expected precipitation. These values and observations of hoarfrost crystals in ice-wedge cracks during summer field surveys indicate that sublimation processes control the formation of ice in wedges, especially at high elevations within this region. © 2010 John Wiley & Sons, Ltd.